Profoundly Diminished Life: The Casualties of Coercion - Morreim, E. Haavi (The Hastings Center report, 1994)
The “futility debate” turns on intractable conflicts of deeply held beliefs about the value of life. It raises practical moral dilemmas of how best to permit parties to honor their own values without coercing unwilling others.